Therapeutic Mask: An Intervention Tool for Psychodrama With Adolescents - Pires, Nuno; Rojas, José Gregório; Sales, Célia M. D.; Vieira, Filipa M. (Frontiers in Psychology, 2021)
Psychodrama is an effective psychotherapeutic model but interventions with adolescents require age-tailored techniques that maximize engagement and facilitate communication processes. This study describes a novel adaptation of a therapeutic mask technique to psychodrama with adolescents. Over the course of eight group sessions of psychodrama, five adolescents (16 to 18 years-old) created their own mask and explored its therapeutic use. Their experiences were captured at the end of each session with the Helpful Aspects of Therapy form, and at the end of the study with the Clinical Change Interview. Awareness/insight/self-understanding, empowerment and relief were the most significant aspects experienced by the adolescents, along with perceived increase of calmness and world connection, satisfaction in interpersonal communication and better emotional expression and regulation. The mask technique was experienced as a playful and engaging task that facilitated insight and interpersonal communication. Findings provide preliminary evidence on the clinical utility of mask-based psychodrama with adolescents.